ANALISIS KINERJA KEUANGAN BANK BCA SYARIAH MENGGUNAKAN PENDEKATANISLAMICITY PERFORMANCE INDEX (PERIODE 2019-2023) - Silvia Wisra Yulia; Tartila Devy (Adisam Publisher, 2025)
This study aims to analyze the financial performance of BCA Syariah banks using the Islamicity Performance Index approach for the 2019-2023 period. So far, the measurement of Islamic bank performance has focused more on indicators similar to conventional banks that assess in terms of financial performance alone. So that a more comprehensive approach is needed such as the Islamicity Performance Index, to assess bank performance from the aspects of justice, halalness, and social welfare in accordance with sharia principles. This study uses quantitative methods with a descriptive approach. This study uses five indicators of Islamicity Performance Index, namely Profit Sharing Ratio, Zakat Performance Ratio, Equitable Distribution Ratio, Islamic Investment vs Non Islamic Investment and Islamic Income vs Non Islamic Income. The population in this study is BCA Syariah bank. Sampling using purposive sampling method at BCA Syariah bank which is available in the Annual Report 2019- 2023. Based on the results of data analysis and discussion, the results showed that the financial performance of BCA Syariah bank for the 2019-2023 period using the Islamicity Performance Index approach showed overall results obtained a score of 4 with a good predicate. Profit Sharing Ratio shows a score of 4 with a good predicate, Zakat Performance Ratio shows a score of 1 with a bad predicate, Equitable Distribution Ratio shows a score of 1 with a bad predicate, Islamic Investment vs Non Islamic Investment shows a score of 5 with a very good predicate, and Islamic Income vs Non Islamic Income shows a score of 5 with a very good predicate.